IL-15 Gene Polymorphism in Celiac Disease Patients and Their Siblings - Kara, Yalçın; Eren, Makbule; Arslan, Serap; Çilingir, Oğuz (Turkish Journal of Gastroenterology, 2021)
Background: Celiac disease (CD) is an immune-mediated enteropathy characterized by lifelong gluten intolerance. Interleukin-15 (IL-15) is a proinflammatory cytokine that is considered a key component in the immune reaction triggered by gluten. Our aim of this studywas to evaluate the influence of IL-15 gene polymorphisms on CD development and clinical presentation.Methods: The study was enrolled-with 90 CD patients (49 female/41 male, median years of age 11), their 38 siblings (20 female/18 male,median years of age 8), and 99 healthy controls (66 female/33 male, median years of age 13). Their demographic findings, symptoms,and signs histopathological grade, Human Leukocyte Antigen (HLA) types were recorded. IL-15 gene polymorphisms rs2857261,rs10519613, and rs1057972 were analyzed through PCR.Results: There was a significantly higher frequency of GG genotype in rs2857972 polymorphisms and TT genotype in rs1057972 polymorphismsin celiac families compared to controls [41% vs. 23% (P = .0008), 36% vs. 11% (P = .001), respectively]. Without consideringtheir HLA status, there was not any difference between celiacs and healthy siblings. However, when stratified according totheir HLADQ2 status, rs2857972 GG polymorphism was 1.5 times prominent in celiacs than siblings at homozygous state, whereasrs1057972 TT genotype was found to be 2.5 times prominent in celiac siblings at heterozygous state. There was no association betweenthese polymorphisms and clinical presentation.Conclusion: rs2857972 GG and rs1057972 TT variants of IL 15 are more prominent in celiac families than controls. However, the impactof IL-15 gene polymorphism on CD development is dependent on HLADQ2 status.